2017
DOI: 10.1002/2017jd027184
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Air Mass Origin on Low‐Cloud Properties in the Southeast Atlantic

Abstract: This study investigates the impact of air mass origin and dynamics on cloud property changes in the Southeast Atlantic (SEA) during the biomass burning season. The understanding of clouds and their determinants at different scales is important for constraining the Earth's radiative budget and thus prominent in climate system research. In this study, the thermodynamically stable SEA stratocumulus cover is observed not only as the result of local environmental conditions but also as connected to large‐scale mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 62 publications
(90 reference statements)
5
30
0
Order By: Relevance
“…On seasonal scales, the spatiotemporal FLC occurrence indicates a connection to the southeastern Atlantic stratocumulus cloud deck. As such, process knowledge from studies on the heavily investigated stratocumulus clouds in this region (e.g., Adebiyi and Zuidema, 2018;Andersen and Cermak, 2015;Diamond et al, 2018;Fuchs et al, 2017Fuchs et al, , 2018Gordon et al, 2018;Painemal et al, 2014;Yuter et al, 2018) may be applicable to Namib-region FLCs, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…On seasonal scales, the spatiotemporal FLC occurrence indicates a connection to the southeastern Atlantic stratocumulus cloud deck. As such, process knowledge from studies on the heavily investigated stratocumulus clouds in this region (e.g., Adebiyi and Zuidema, 2018;Andersen and Cermak, 2015;Diamond et al, 2018;Fuchs et al, 2017Fuchs et al, , 2018Gordon et al, 2018;Painemal et al, 2014;Yuter et al, 2018) may be applicable to Namib-region FLCs, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…While the aerosol index may be a better proxy for cloud condensation nuclei than AOD (Stier, 2016), its computation requires the Ångström exponent, which is not available in the 8-day MODIS L3 product (Levy et al, 2013). Studies that observed the bivariate relations between AOD and cloud properties are numerous (e.g., Kaufman, 2005Kaufman, , 2006Grandey et al, 2013), but spurious correlations exist. The strength of the relation between AOD and CF or REF is depending on satellite artifacts in the vicinity of clouds, e.g., cloud contamination and three-dimensional radiative effects (Várnai et al, 2013;Christensen et al, 2017) as well as on meteorological conditions, e.g., aerosol hygroscopic swelling with humidity Quaas et al, 2010).…”
Section: Predictor Selectionmentioning
confidence: 99%
“…In this context, the coastal southern Africa region is arguably one of the regions where the aerosol-radiation-cloud interactions are strongest in the world (Adebiyi et al, 2015;Fuchs et al, 2017). However, state-of-the-art climate models diverge by several W m −2 when attempting to calculate the regional direct radiative effect over coastal southern region (Myhre et al, 2013;Stier et al, 2013) ranging from negative (−3 W m −2 ) to strong positive forcing (+5 W m −2 ) for mean seasonal averages.…”
Section: Introductionmentioning
confidence: 99%